COVID-19 and the plight of the migrant worker in India. Issue 5 (20th October 2021) - Alam, Mahfooz; Zaini, Syed Hameedur Rahman
ABSTRACT: COVID-19 has affected the lives of entire populations across the globe. Different sections of the society have been impacted, some more than others. In the context of India, which has a sizeable number of people living in adversity, the impact of COVID-19 has been more pronounced in the sub-section of 'migrant workers'. Due to the imposed lockdowns to contain the spread of the coronavirus, these workers have lost their jobs and the insecurity has led them to return to their home villages in arduous conditions. Their plight is showcased here which also exposes the role of the government which has been largely indifferent and reactionary at best. The article is based on secondary research and offers certain takeaways about how emergency situations need to be handled differently to ensure no particular section is neglected.